2008
DOI: 10.3390/s8021297
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a nrdA::luxCDABE Fusion and Its Use in Escherichia coli as a DNA Damage Biosensor

Abstract: The promoter of nrdA gene which is related with DNA synthesis was used to construct a DNA damage sensitive biosensor. A recombinant bioluminescent E. coli strain, BBTNrdA, harboring a plasmid with the nrdA promoter fused to the luxCDABE operon, was successfully constructed. Its response to various chemicals including genotoxic chemicals substantiates it as a DNA damage biosensor. In characterization, three different classes of toxicants were used: DNA damaging chemicals, oxidative stress chemicals, and phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The ribonucleoside diphosphate reductase encoding nrdB is part of the nrdAB operon that is involved in DNA replication and repair by reducing ribonucleotides to deoxyribonucleotides. The E. coli nrdA promoter was found to respond strongly to DNA damaging chemicals and is suggested to function as a biosensor for DNA damage [36] . It is possible that this operon has a comparable function in Salmonella Typhimurium and that the operon is expressed upon DNA damage induced in the hostile porcine environment.…”
Section: Resultsmentioning
confidence: 99%
“…The ribonucleoside diphosphate reductase encoding nrdB is part of the nrdAB operon that is involved in DNA replication and repair by reducing ribonucleotides to deoxyribonucleotides. The E. coli nrdA promoter was found to respond strongly to DNA damaging chemicals and is suggested to function as a biosensor for DNA damage [36] . It is possible that this operon has a comparable function in Salmonella Typhimurium and that the operon is expressed upon DNA damage induced in the hostile porcine environment.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 NrdA is involved in DNA biosynthesis and converts ribonucleotides to deoxyribonucleotides, acting as a DNA damage biosensor. 33 To verify the potential involvement of the two candidate proteins in patulin biodegradation, ahpC and nrdA knockout mutants of TT-09 were constructed via allele exchange, and their ability to degrade patulin was determined. Results demonstrated that ΔnrdA mutants completely lost the ability to degrade patulin, while ΔahpC mutants did not alter the ability of the mutant strain of TT-09 cells to degrade patulin (Figure 6C,D).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Of the two proteins, AhpC belongs to a large family of peroxidases and is typically induced by oxidative stress to protect cells against various abiotic stresses, such as heat, salt, pesticides (carbofuran), heavy metals, and UV-B. , NrdA is involved in DNA biosynthesis and converts ribonucleotides to deoxyribonucleotides, acting as a DNA damage biosensor . To verify the potential involvement of the two candidate proteins in patulin biodegradation, ahpC and nrdA knockout mutants of TT-09 were constructed via allele exchange, and their ability to degrade patulin was determined.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al [ 20 ] constructed strain BBT NrdA , which is an E. coli based lux strain that has the nrdA gene as the promoter. The nrdA gene is activated in DNA synthesis, but is not regulated by the SOS response.…”
Section: Effect-specific Lux Strainsmentioning
confidence: 99%